ARAH BARU SUPERVISI PENDIDIKAN ISLAM DI INDONESIA - Jaelani, Dian Iskandar (e-Journal STAI Muhammadiyah Tulungagung, 2013)
Several studies on the quality of education is often also called the school to study the effect of output ( output ) inferred by Suryadi education that , in developing countries the influence of school and teacher quality on student achievement is greater than the influence of the same factors in developed countries , but in developing countries the influence of family background on learning achievement is smaller. There are still many shortcomings in the Indonesian education system compared to the Finnish education system is in the form of small start of school board regulations for the students. Indonesia can still improve and review the education system that has long been used in Indonesia, so the education system in Indonesia could rise to at least rank qualification assessment by an international board of education. With so Indonesia can be proud of the education system, as well as with the quality of education in Indonesia will be juxtaposed with other countries in the world. Improving the quality of education in schools requires professional education and systematic in their objective. Effectiveness of educational activities in a school influenced many variables (both concerning the personal aspects, operational, and material) that need to get training and development in a sustainable manner. Coaching and development process is an assessment of the overall situation of education supervision .